Determinant factors of partisans' confirmation bias in social media - Rahkman Ardi; Adismara Putri Pradiri (HUMANITAS: Indonesian Psychological Journal, 2021)
Partisans are more likely to be motivated by a desire to justify their political opinion which is called as confirmation bias. This research aimed to investigate the determinant factors of confirmation bias among college students who actively obtained political information in social media. All participants were associated with a student organization of particular political ideologies. The determinant factors of confirmation bias under investigation were critical thinking, consisting of two dimensions-i.e., critical openness and reflective skepticism; authoritarian personality; collective entitlement; and political preference. A confirmation bias scale pertaining to media reporting was specifically constructed for the purpose of this study. The measurement of critical thinking, authoritarian personality, and collective entitlement utilized existing instruments. The sample in this study was 95 students with various political ideologies. Hierarchical multiple regression analysis was conducted to analyze the data. The current study results demonstrated that critical openness, collective entitlement, and authoritarian personality were predictors of confirmation bias. Meanwhile, reflective skepticism and political preference were not significant predictors. The findings could be the building blocks for developing an intervention to increase digital citizenship awareness by open-mindedness to reduce confirmation bias among social media users